A systematic review of definitions of motor vehicle headways in driver behaviour and performance studies. (February 2021) - Biswas, Raaj Kishore; Friswell, Rena; Olivier, Jake; Williamson, Ann; Senserrick, Teresa
Highlights: Studies of safe driver behaviour and performance use varied definitions of headway. From 1980, less than half of 110 reviewed studies provided reproducible definitions. Definitions often depended on the measuring method, contributing to reporting gaps. Vehicle length should be excluded when measuring headway as a safety behaviour. Measurement points for both vehicles and device accuracy should always be reported. Abstract: Headway is a safety measure commonly used to investigate driving behaviour and driver performance. Its purpose is to reflect the following distance or time between a leading and following vehicle in traffic. It is therefore associated with drivers' response time, such as in braking or swerving, during safety critical events. In the literature, distance and time headway are defined in different ways, despite standard definitions in the traffic engineering literature, which prompted this systematic review of headway definitions across a range of study designs, in order to recommend approaches to improve the accuracy and reproducibility of headway definitions used in road safety contexts. PRISMA guidelines were followed to search four databases (EMBASE, COMPENDEX, SCOPUS and MEDLINE) for studies that reported on headways or discussed methodological approaches. The search and filtering of abstracts identified 110 articles for a qualitative synthesis. Four broad approaches to measuring headways were detected: studies using simulation, roadside external features, on-road features, and on-vehicle features. Studies were coded as to whether they included written explanation, mathematical statements, or pictorial depictions of headway. Only 49.6% of studies contextualised headway sufficiently for reproducibility. Reproducibility is crucial for accurate interpretation of research findings and comparisons across studies. It is recommended that headway definitions should a) exclude vehicle or parts of vehicle lengths, b) include reference points (e.g., bumper/axle/rear), c) have a consistent terminology, and d) include the accuracy of headway measuring devices to report the precision of a study's findings.